Invitation ? RMCMI 1995 ? 1996 Board of Directors (Rocky Mountain Coal Mining Institute, 1995)
Marcie A. Greenberg RMCMI PRESIDENT 1995-1996 on behalf of the RMCMI Board of Directors and Officers of The Rocky Mountain Coal Mining Institute cordially invites you and your family to attend the 92nd Regular Meeting and Convention to be held June 30 thru July 2, 1996 Durango, Colorado